LAJU DEGRADASI SURFAKTAN LINEAR ALKIL BENZENA SULFONAT (LAS) PADA LIMBAH DETERJEN SECARA ANAEROB PADA REAKTOR LEKAT DIAM BERMEDIA SARANG TAWON - Nida Sopiah (Jurnal Teknologi Lingkungan, 2006)
Linear alkylbenzene sulfonate (LAS) represents one of active substanceof surfactants in detergents of which in high concentrations may causeenvironmental pollutions. The aim of the research was to know theefficiency of exclusion of LAS and the rate of LAS degradation indetergent wastes by the anaerobic process at fixed bed reactor equippedwith cross flow material. This research was done in Process Laboratory ofBalai Teknologi Lingkungan BPPT PUSPIPTEK Serpong. Reactoroperation was done through continuous process with close circulation, upflow and 5 hours Rate Time Hour (RTH). Exclusion of LAS of detergentwaste was recorded for 17 days. The degree of acidity after the processwithout inoculum (P1.0) was to 8.45, and for an anaerob condition withadded inoculum (P1.1) was 7.88. The efficiency of the highest exclusionof CO soluble was equal to 80.96% (P1.1) with effluent 476 mg/L, and 76.81 % (P1.0) with effluent 531 mg/L. The exclusion of LAS of detergentwastes was 99.19% (P1.1) with LAS effluent equal to 17.51 mg/L and98.3% (P1.0) with LAS effluent equal to 27.84 mg/L. The maximum rate ofLAS surfactant degradationunt 0.95 ppm/day (P1.1) and 0.44 ppm/day(P1.0).